BIMBINGAN DAN KONSELING DALAM ISLAM - Sukatin; Livya; Salwa Nafisya (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2026)
Islamic Guidance and Counseling is a continuous process of providing assistance to help individuals develop their fitrah and achieve happiness in this world and the hereafter. This article discusses the techniques of guidance and counseling in Islam, the urgency of Islamic guidance and counseling in education, and the principles of Islamic guidance and counseling. The results show that Islamic guidance and counseling are very important in helping individuals achieve educational goals and form a useful personality in life‎.